INVERS MATRIKS CENTROSYMMETRIC BENTUK KHUSUS ORDO n×n (n≥3) MENGGUNAKAN ADJOIN - Ade Novia Rahma; Ricken Husnudzan Vitho; Rahmawati Rahmawati; Elfira Saftri (LPPM Universitas Bina Bangsa, 2023)
A matrix is a collection of numbers that are often also called regularly arranged entries by rows and colums. There are several types of matrices, such as Centrosymmetric matrix. The concept of a matrix is very useful in solving some problems in mathematics. One of the most common problems in mathematics is solving system of linear equations. One way to determining the inverse of a matrix is using a Adjoin Method. This study aims to determine the inverse of a Centrosymmetric matrix of a special shape using the Adjoin Method